Between voodoo science and adaptive management: the role and research needs for indicators of sustainable forest management - Prabhu, Ravi; Ruitenbeek, H.J.; Boyle, T.J.B.; Colfer, C.J.P. (CAB International, 2001)
The development of appropriate indicators of sustainable forest management is attracting considerable interest, although some controversy still exists regarding their utility. The wrong indicators can lead to negative, destructive effects on the systems whose maintenance they allegedly seek to support, and in order for indicators to fulfil a legitimate rule as information tools for forest managers, attention needs to be paid to their proper selection, development and use. This chapter examines how these condition can be met. As all definitions of sustainability involve value judgements we advise caution when establishing objective and scientifically based indicators, if the assumption thereby is that such indicators might deliver value-neutral information. Attention therefore must be paid to underlying mental models and subjectivity. If indicator sets are to fulfil their goal they must be both transparent and accepted by society. A hierarchical approach remains currently the most practical and effective model for dealing with criteria and indicators (C&I). C&I sets might, however, be better considered as information or communication networks as such, C&I would allow us recognize information related to systemic sustainability. thresholds for individual indicators are important as they could theoretically indicate switch points or inflection zones for the system, including points at which the system degrades irretrievably. One major challenge facing researchers is the identification and quantification of such thresholds. Adaptive co-management is emerging as a promising means of resource management, but there is little understanding of how to maximize its contribution to sustainable tropical forest management. our vision is that, whole C&I would eventually become an integral part of the monitoring and feed back systems. thus facilitating adaptive co-management..It is concluded that , while indicators suffer from limitations in providing broad but not deep insights, their advantages as effective information tool in the service of forest management outweigh these limitations, They are transparent and readily understandable information tools and their scope is limited only by the extent of our knowledge of the underlying systems and translation of that knowledge into effective indicators.